فعالية حقن البلازما الغنية بالصفيحات (PRP) ضمن جلد فروة الرأس في علاج الحاصة الأندروجينية عند الذكور - حسن, فوز; سليمان, حميد; يسير, سمر (Latakia University Journal -Medical Sciences Series, 2019)
Background: Androgenetic alopecia (AGA) is a common problem, which has limited options for treatment. Platelet rich plasma (PRP) has recently been suggested as an adjunctive therapy for it. Objects: to assess the effectiveness of PRP in males with AGA. Patients & methods: This before and after study included 30 males with AGA of the types I to V according to Norwood's classification, who didn't apply any other treatment for the AGA for the past 3 months. They were between 17 and 42 years old. Each patient received a total of 3 treatments with Cacl2-activated PRP at one-month intervals, with a follow up period for 6 months after the first session. The efficacy was evaluated by measuring hair density manually in 1 cm2 of the scalp by the use of dermatoscope. Then a comparison between hair density average values before, after 2 and 6 months of the first session was made. Results: Hair density increased from 172.46 ± 59.04 before treatment to 206.06 ± 70.77 after 2 months, and that was maintained after 6 months with a mean of 205.53 ± 68.20 hair/cm2, so the mean increase of hair density was 19.17% with no significant side effects. Type III vertex had the least treatment response, and there was no correlation between treatment response and either patient's age or duration of alopecia. Conclusion: PRP injection for men with AGA has a positive effect on hair density with minimal side effects. ضمت الدراسة 30 مريضاً من الذكور المصابين بحاصة أندروجينية من النمط I إلى V حسب تصنيف نوروود، تراوحت أعمارهم بين 17 و42 سنة. تمت معالجتهم عبر حقن البلازما الغنية بالصفيحات المفعلة بكلوريد الكالسيوم ضمن جلد فروة الرأس بمعدل 3 جلسات يفصلها شهر مع متابعتهم لمدة 6 أشهر بعد الجلسة الأولى لتقييم الفعالية. قُيِّمَتْ فعالية الحقن عبر تعداد كثافة الأشعار يدوياً في 1 سم2 من الفروة ثابت عند كل مريض بعد تكبيره بوساطة منظار الجلد وتصويره فوتوغرافياً، وتم إجراء مقارنة بين قيم الكثافة قبل الحقن وبعد شهرين و6 أشهر من الجلسة الأولى. وجدنا أن حقن الـ PRP قد أدى إلى زيادة هامة إحصائياً في كثافة الشعر بعد شهرين من بدء المعالجة وتمت المحافظة على هذه النتيجة بعد 6 أشهر وكان متوسط الزيادة 19.17% دون حدوث آثار جانبية هامة، وإن أغلب الذين استجابوا للعلاج قد حصل لديهم تحسن في الكثافة تراوح بين 10 - 20% وكان النمط III القمي أقل الأنماط استجابة للعلاج بينما لم نجد علاقة بين الاستجابة للعلاج وكل من عمر المريض أو مدة الحاصة.